REPRESENTASI TOXIC RELATIONSHIP DALAM FILM SAMPAI JUMPA SELAMAT TINGGAL - Rena Zakia; Muhamad Hasan Basori (KAGANGA KOMUNIKA: Journal of Communication Science, 2026)
Representation is often conveyed through various media, one of which is film. Sampai Jumpa, Selamat Tinggal (2025) portrays the dynamics of toxic relationships through conflicts between its characters. The film not only presents a story of search and uncertainty within a relationship, but also illustrates various forms of unhealthy relationships. The growing concern over toxic relationships as a social issue is reflected in this film through the experiences of the characters Wyn and Dani. This study employs a qualitative descriptive method using Charles Sanders Peirce’s semiotic approach, which emphasizes the triadic relationship between representamen, object, and interpretant, as well as the classification of signs into icons, indexes, and symbols. The findings reveal that toxic relationships are represented through various unhealthy behaviors, such as emotional neglect (ghosting), emotional manipulation through shifting blame, destructive communication, verbal and nonverbal abuse, and relational imbalance. These representations are constructed through the integration of visual and verbal signs that depict unstable, pressuring, and psychologically harmful relationships. The findings indicate that film not only reflects social reality but also shapes audience understanding of unhealthy interpersonal relationship dynamics.   Keywords: Film, Representation, Semiotics, Toxic Relationship